Confocal Microscopy for Detection of Intracellular Bacteria in Urine Samples of patients Suspected with Urinary Tract Infection: A Cross-sectional Observational Study - Bhagyashri Patil-Takbhate; Nilam Memane; Srikanth Tripathy; Nageswari Gandham; Shahzad Mirza (Journal of Clinical and Diagnostic Research)
Introduction: Uropathogenic bacteria like Escherichia coli (UPEC) and Pseudomonas are the most common agents of Urinary Tract Infection (UTI). Recently, the ability of UPEC to invade urothelial cells and to form Intracellular Bacterial Communities (IBCs) has been described which can be missed out during routine diagnosis and can lead to recurrent infection despite antibiotic treatment. Aim: To study the presence of ICB in exfoliated urothelial cells using confocal microscopy. Materials and Methods: A cross-sectional observational study was conducted at Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pune, Maharashtra, India for detection of Isolated Intracellular Bacteria (IIB) and IBC. The study done for detection of IIB/IBC in urine samples suspected with UTI between January 2022 to December 2022. Four hundred ninety-five urine samples collected from women of age group 18-50 years visited at Central laboratory for suspected diagnosis of UTI. Urine samples were screened for detection of Gram-negative intracellular bacteria by using light microscopy. Urine samples showing intracellular gram-negative bacteria by Gram staining were further processed for fluorescence confocal microscopy followed by conventional culture and virulence detection by multiplex Polymerase Chain Reaction (PCR). Formation of biofilm ability was assessed by tube method. Quantitative data presented as mean and Standard Deviation (SD) while qualitative variables expressed as frequency (percentage). Results: Ninety-two Gram negative urine samples were processed for fluorescence staining and culture, out of that 24 were processed for virulence gene detection. Mean age of women was 36.2±9.5 years and 74 (80.4%) had fever, 19 (20.7%) had burning sensation and 16 (17.4%) had frequent micturition. Confocal microscopy examination showed 23 (25.0%) samples which were IIB and 11 (12.0%) were IBC. While the culture report showed 23 (25.0%) were E. coli, 29 (31.5%) were polymicrobial flora and 29 (31.05%) were negative for culture. Interestingly, out of 29 culture negative samples 9 (3.1%) were detected with IIB and IBC by confocal microscopy. Prevalence of virulent genes like iutA was higher 12 (50.0%). Conclusion: This study highlighted the importance of confocal microscopy for diagnosis of IIB/IBC which was missed by urine culture. Unrecognised bacterial colonisation might be maintained through intracellular reservoir. Hence diagnosis of IIB/IBC is crucial for the management of recurrent UTI and precise antibiotic therapy to avoid antibiotic resistance.